Improvement in the purification of roof water harvesting system - BLESSY V. A MUNNA P. V; Dr. Sathian K. K (Guide) (Tavanur 2015 Department of Land and Water Resources & Conservation Engineering)
As roof water carries impurities, purification of this water is a must to make it acceptable for domestic use. the efficiency of the 60 micron filter is high with a value of 86.2%.first flush system is found to be effective in removing the higher concentration of impurities from the initially generated roof water. first flush system along with 60u filter is found to be more effective in purifying the roof water, compared to 100u mesh filter.
Improvement in the purification of roof water harvesting system